2004
DOI: 10.1097/01.brs.0000142008.49907.c7
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Neurologic Function Following Nontraumatic Spinal Cord Lesions in Israel

Abstract: The prognosis for neurologic recovery is affected mainly by SCL severity and etiology, and is usually better in NTSCLs than in TSCLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 13 publications
3
46
2
Order By: Relevance
“…The substantial similarity between the two groups in both AIS and motor scores improvement is particularly noteworthy. In a large retrospective study involving 1085 non-traumatic patients and 250 traumatic ones, Catz et al 7 found a better prognosis for neurological recovery (evaluated as AIS impairment increase) in non-traumatic patients. This study do not confirm this finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The substantial similarity between the two groups in both AIS and motor scores improvement is particularly noteworthy. In a large retrospective study involving 1085 non-traumatic patients and 250 traumatic ones, Catz et al 7 found a better prognosis for neurological recovery (evaluated as AIS impairment increase) in non-traumatic patients. This study do not confirm this finding.…”
Section: Discussionmentioning
confidence: 99%
“…However, in spite of the high incidence of non-traumatic lesions, which is considered to vary between 25 and 80% of the total admission for spinal cord injuries, there are still few studies on the influence of different etiologies (namely traumatic vs non-traumatic) on SCL outcome; [5][6][7][8][9][10][11] this is probably due to the different features of the two populations with regard to age, lesion severity and lesion to admission time (LTA), which are wellknown prognostic factors: 5 therefore, the two groups of patients are poorly comparable.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12] Most such studies, however, examined metastatic spinal cord compression only, and although they have demonstrated the benefits of rehabilitation in neoplastic patients with regard to pain, independence, prevention of complications and survival, they failed to make comparisons with traumatic SCI (TSCI) patients. [5][6][7][9][10][11][12] Thus, few studies have compared the outcomes of NSCI and TSCI patients, likely because of differences in prognostic factors (age, lesion severity and level, and lesion-to-rehabilitation hospital admission time) between these groups that render them incomparable.…”
Section: Introductionmentioning
confidence: 99%
“…Catz 8 observed that the odds of any neurological recovery and functional neurological recovery are significantly higher in patients with neoplastic disease than in patients with traumatic lesions. The studies that we have discussed, however, were conducted in completely different settings from those of the present study, particularly with regard to the length of rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…66,67 Thus, it is well recognised that there is substantial improvement in clinical signs in many human patients that suffer incomplete SCI, [68][69][70] which can, indeed, complicate analysis of clinical trials of novel therapeutic interventions. 71,72 However, in common with human SCI patients, there is a subpopulation of affected dogs in which recovery is incomplete or does not occur at all; these affected dogs can be identified with reasonable certainty at an early stage after injury because they lose all sensory and motor function in the hindquarters and pelvic limbs.…”
Section: Treatment and Prognosismentioning
confidence: 99%